Biology of scale carp and grass carp. 1. Length-weight relationship and growth performance under the agroclimatic zone 1 of Himachal Pradesh - Dhanze, Rani; Dhanse, J R (Indian Journal of Fisheries, 2011)
Biology of scale carp (Cyprinus carpio communis) and grass carp (Ctenopharyngodon idella) studied under the agroclimatic condition of zone 1 of Himachal Pradesh deduced two separate equations for the length-weight relationship as W = 1.2735 x 10" SL27433, r = 1.0032; W = 2.6813xl05 TL29002’ r = 0.9980 and W = 2.2123x10-" SL25669, r = 0.9961; W = 3.7261x105 TL27988, r = 1.0401 respectively. The perfection of these equations was confirmed by back calculation of the weight and its comparisons with the observed weight. Growth performance of these two species was also studied for a period of eight months in this region and as a result the incremental growth per month has been computed as 14.1 and 82.23 g for C. carpio communis and C. idella respectively. The analysis and correlation of these data revealed that the grass carp has better yield efficiency as compared to scale carp for culture fisheries in the State. The existing stock of scale carp has been genetically degraded due to the repeated inbreeding which led to the poor yield per unit area in this zone.